Excision of Os Trigonum in Dancers via an Open Posteromedial Approach. Issue 4 (October 2018) - Heyer, Jessica H.; Dai, Amos Z.; Rose, Donald J.
Abstract : An os trigonum is a potential source of posterior ankle pain in dancers, often associated with flexor hallucis longus (FHL) pathology. Surgical excision is indicated on failure of nonoperative management. Options for surgical excision include open excision (via a posterolateral or posteromedial approach), subtalar arthroscopy, and posterior endoscopy. Os trigonum excision via an open posteromedial approach with concomitant FHL tenolysis/tenosynovectomy is a safe and effective method for the operative treatment of a symptomatic os trigonum that allows for identification and treatment of associated FHL pathology. The major steps in the procedure, which are demonstrated in this video article, are: (1) preoperative planning with appropriate imaging; (2) patient is positioned in a supine position with the operative extremity in figure-of-4 position; (3) a 3-cm, slightly curvilinear longitudinal incision is made midway between the posterior aspect of the medial malleolus and the anterior aspect of the Achilles tendon, over the palpated FHL tendon, and the flexor retinaculum is exposed and incised; the neurovascular bundle is retracted anteriorly, exposing the FHL tendon and sheath; (4) FHL tenolysis/tenosynovectomy is performed; (5) the FHL is retracted anteriorly and a capsulotomy is performed over the os trigonum and the os trigonum is excised; (6) the capsule is repaired and closure is performed; and (7) dressings and a CAM (controlled ankle motion) walking boot are applied. The patient begins physical therapy at 2 weeks postoperatively and may return to dance at 4 to 6 weeks postoperatively as tolerated. In our series of 40 cases, 95% of patients who desired to return to dance were able to return to their pre-injury level of dance. There were no major neurovascular complications.